Effects of Gymnema lactiferum Leaf on Serum Glucose and Cholesterol Levels of Normo-glycaemic Wistar Rats - Bandara, W.V.R.T.D.G.; Ekanayake, S.; Jansz, E.R.; Balasubramanium, K. (My University, 2010)
Gymnema lactiferum var. lactiferum is a twining plant which belongs to the family Asclepiadaceae (milk weed family). This plant is distributed in many South Asian countries including, Assam, Malay Peninsula, Malaysia and Sri Lanka. It is reported that G. lactiferum leaf powder is used popularly by the people in Jaffna, as a treatment for diabetes. The present study indicates that the leaf powder does not result in a significant reduction of FBS (p=O.64) or serum total cholesterol Levels (p=0.49) when tested with normo-gLycaemic Wistar rats following feeding for 4 weeks. Further the leaf extract did not produce any significant effect on blood glucose levels on the glucose challenge (p=O.26) in the normo-glycaemic Wistar rats.
Keywords: Gymnema lactiferum var; Lactiferum; Normo-glycaemic rats; Blood glucose; Cholesterol